Love warrior : a memoir - Melton, Glennon Doyle, 1976- (New York : Flatiron Books, 2016)
Traces the author's journey of self-discovery after the dissolution of her marriage, revealing how she found healing by rejecting gender standards and refusing to settle for a "good-enough" life.
"A memoir"--Jacket.
"Oprah's Book Club, 2016 selection."--Book cover.
Keywords: Melton, Glennon Doyle, -- 1976- -- Marriage; Melton, Glennon Doyle, -- 1976- -- Divorce; Divorced women -- United States -- Biography